2013
DOI: 10.1016/j.surg.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Surgical-site infection after abdominal wall closure with triclosan-impregnated polydioxanone sutures: Results of a randomized clinical pathway facilitated trial (NCT00998907)

Abstract: This clinical pathway facilitated trial shows that triclosan impregnation of a 2-0 polydioxanone closing suture can decrease wound infections in patients having a laparotomy for general and abdominal vascular procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 41 publications
0
71
0
5
Order By: Relevance
“…Moreover, it has been reported that the Fabl gene encodes the enoyl-acyl carrier protein reductase enzyme, which is essential in bacterial fatty acid biosynthesis; triclosan is a Fabl inhibitor and therefore inhibits fatty acid biosynthesis [16]. Therefore, triclosan can reduce 90% to 99.9% of the inoculates of E. coli and Staphylococcus aureus [10,17]. However, some bacteria have shown a certain resistance to triclosan, such as Pseudomonas aeruginosa, which possesses multi-drug efflux pumps that remove triclosan from the cell [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the Fabl gene encodes the enoyl-acyl carrier protein reductase enzyme, which is essential in bacterial fatty acid biosynthesis; triclosan is a Fabl inhibitor and therefore inhibits fatty acid biosynthesis [16]. Therefore, triclosan can reduce 90% to 99.9% of the inoculates of E. coli and Staphylococcus aureus [10,17]. However, some bacteria have shown a certain resistance to triclosan, such as Pseudomonas aeruginosa, which possesses multi-drug efflux pumps that remove triclosan from the cell [16].…”
Section: Discussionmentioning
confidence: 99%
“…No reduction in the incidence of surgical site infection was reported (OR 0.91: CI 0.66-1.25; p = 0.39). Four other RCT's have compared sutures with or without triclosan in laparotomy closure, either with polyglactin sutures (Vicryl) [73,74] or with polydioxanone (PDS) [75,76]. A meta-analysis on all five studies performed by Diener et al showed a significant decrease in surgical site infection (OR 0.67: CI 0.47-0.98).…”
Section: Sutures Impregnated With Antibioticsmentioning
confidence: 99%
“…Vicryl Plus, have resulted in a highly efficient defense against various bacterial pathogens [11], [12]. In vivo studies for sternum surgery [13], abdominal wall closure [14], and cerebrospinal fluid shunting procedures [15] indicate significantly lower infection rates for surgical interventions using triclosan coated anti-microbial sutures [16]. In contrast, for some indications there is an ongoing controversial discussion [10], [17], such as appendicitis, breast cancer and colorectal surgery [4], [18]–[20].…”
Section: Introductionmentioning
confidence: 99%